PvUPS1, an allantoin transporter in nodulated roots of French bean - Pélissier, Hélène C.; Schumacher, Karin (Plant physiology, 2004)
Nodulated legumes receive their nitrogen via nitrogen-fixing rhizobia, which exist in a symbiotic relationship with the root system. In tropical legumes like French bean (Phaseolus vulgaris) or soybean (Glycine max), most of the fixed nitrogen is used for synthesis of the ureides allantoin and allantoic acid, the major long-distance transport forms of organic nitrogen in these species. The purpose of this investigation was to identify a ureide transporter that would allow us to further characterize the mechanisms regulating ureide partitioning in legume roots. A putative allantoin transporter (PvUPS1) was isolated from nodulated roots of French bean and was functionally characterized in an allantoin transport-deficient yeast mutant showing that PvUPS1 transports allantoin but also binds its precursors xanthine and uric acid. In beans, PvUPS1 was expressed throughout the plant body, with strongest expression in nodulated roots, source leaves, pods, and seed coats. In roots, PvUPS1 expression was dependent on the status of nodulation, with highest expression in nodules and roots of nodulated plants compared with non-nodulated roots supplied with ammonium nitrate or allantoin. In situ RNA hybridization localized PvUPS1 to the nodule endodermis and the endodermis and phloem of the nodule vasculature. These results strengthen our prediction that in bean nodules, PvUPS1 is involved in delivery of allantoin to the vascular bundle and loading into the nodule phloem.
Gesehen am 10.08.2017